Enhanced Tubulation of Liposome Containing Cardiolipin by MamY Protein from Magnetotactic Bacteria. Issue 12 (14th August 2018) - Tanaka, Masayoshi; Suwatthanarak, Thanawat; Arakaki, Atsushi; Johnson, Benjamin R. G.; Evans, Stephen D.; Okochi, Mina; Staniland, Sarah S.; Matsunaga, Tadashi
Abstract : Lipid tubules are of particular interest for many potential applications in nanotechnology. Among various lipid tubule fabrication techniques, the morphological regulation of membrane structure by proteins mimicking biological processes may provide the chances to form lipid tubes with highly tuned structures. Magnetotactic bacteria synthesize magnetosomes (a unique prokaryotic organelle comprising a magnetite crystal within a lipid envelope). MamY protein is previously identified as the magnetosome protein responsible for magnetosome vesicle formation and stabilization. Furthermore, MamY is shown in vitro liposome tubulation activity. In this study, the interaction of MamY and phospholipids is investigated by using a lipids‐immobilized membrane strip and a peptide array. Here, the binding of MamY to the anionic phospholipid, cardiolipin, is found and enhanced liposome tubulation efficiency. The authors propose the interaction is responsible for recruiting and locating cardiolipin to elongate liposome in vitro. The authors also suggest a similar mechanism for the invagination site in magnetosomes vesicle formation, where the lipid itself contributes further to increasing the curvature. These findings are highly important to develop an effective biomimetic synthesis technique of lipid tubules and to elucidate the unique prokaryotic organelle formation in magnetotactic bacteria. Abstract : Lipid tubules are of particular interest for many potential applications in nanotechnology. In this study, the binding between a magnetosome protein, MamY, to the anionic phospholipid, cardiolipin, is found and enhances liposome tubulation efficiency. These results are highly important to develop an effective biomimetic synthesis technique of lipid tubules and to elucidate the unique prokaryotic organelle formation in magnetotactic bacteria. This article is part of an AFOB (Asian Federation of Biotechnology) Special issue. To learn more about the AFOB visitwww.afob.org .